SALES FORCE PERFORMANCE EFFECTIVENESS TRAINING IN SMES - Ardiansyah Rasyid; Levina Setiawan; Johanna Aurielle Mardjo (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2024)
Achieving good sales performance will result from the performance of the sales force. Sales force performance is an evaluation of the sales force's contribution to achieving organizational goals. The purpose of the activity is to conduct a performance assessment of SMEs. Partners who become the place of activity are culinary creative product businesses in Jambi city. In improving business performance, through provision of knowledge on how to assess business performance that has been run. Based on the analysis of partner problems, there is still weak knowledge of performance appraisal so that it has not been able to achieve competitive advantage. The method offered in this activity is to implement a performance assessment instrument in the form of socialization and assistance to business owners. The outcomes of the exercise indicate that the salesperson performance training has been successful. By evaluating business performance, partners are now aware of areas for improvement to enhance business competitiveness and tackle growing competitive challenges effectively.